Construction of American Hunger in Richard Wright's Novel "Black Boy" (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2019)
This study aims at explaining the construction of American hunger in Richard Wright’s novel Black Boy. This study is a qualitative analysis that relies on the power of word or explanatory reasoning. The data were collected by reading, identifying, classifying and analyzed using the structualism theories which used in this study by relating to binary operation to see the gap between black and white society. The results of this study were the segregation between black and white people in terms of the treatment, power, and superiority that in the end, it resulted that the black people are being treated different and has no right for freedom. The American Hunger is described in the novel through some events that go in the opposite between black and white people. The tention between them revealed from the different treatment, oppression, discrimination, superiority, and hunger that the black and white people or society experienced. The dominance and the power of the white people had harm the black people in some aspects in their life. Second, American Hunger that was described in the novel was regarded as the desire of the black people when they were living side by side with the white people in America. When the discrimination, segregation, and oppression occurs toward the black people, they satisfied their American hunger by standing agaisnt racial oppression, strengthen the superiority, and against the hunger. Keywords: American hunger, construction, discrimination, structuralism